2010
DOI: 10.2190/pm.40.2.c
|View full text |Cite
|
Sign up to set email alerts
|

It's Not over When it's Over: Long-Term Symptoms in Cancer Survivors—A Systematic Review

Abstract: Based on longitudinal and cross-sectional evidence, cancer survivors can experience symptoms for more than 10 years following treatment. These symptoms were present in survivors of all four cancer types who underwent a wide variety of treatment. The results indicate that these symptoms should be evaluated and managed to optimize long-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
396
1
18

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 567 publications
(431 citation statements)
references
References 100 publications
(172 reference statements)
16
396
1
18
Order By: Relevance
“…The literature provides evidence that being a cancer survivor very often means having to face late-presenting and/or long-term effects, both psychosocial and physical, that can impact different QoL domains years after treatment ends. Musculoskeletal problems, pain, sexual dysfunction, fatigue, anxiety, depressive symptoms, and cognitive limitations are some of the effects which can be found during treatment, and which can also affect long-term cancer survivorship [3][4][5][6]. More specific long-term effects such as relapses, iatrogenic tumors, fear of cancer recurrence, and limitations in restarting one's pre-illness functioning, are frequently denounced by survivors [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The literature provides evidence that being a cancer survivor very often means having to face late-presenting and/or long-term effects, both psychosocial and physical, that can impact different QoL domains years after treatment ends. Musculoskeletal problems, pain, sexual dysfunction, fatigue, anxiety, depressive symptoms, and cognitive limitations are some of the effects which can be found during treatment, and which can also affect long-term cancer survivorship [3][4][5][6]. More specific long-term effects such as relapses, iatrogenic tumors, fear of cancer recurrence, and limitations in restarting one's pre-illness functioning, are frequently denounced by survivors [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the direct and long-term effects of cancer and its treatment, most survivors do not return to their previous state of well-being [4,5]. Cancer survivors suffer from a range of problems, varying from fatigue, reduced physical fitness, and psychological problems to symptoms related to specific cancer types, such as lymphedema or difficulties with speaking and swallowing after head and neck surgery [6].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the WHOQOL-BREF (2004b) measures physical health, psychological health, self-esteem, sexual health, social relationships and environment. Cancer survivors generally report lower QOL scores than matched individuals without cancer (Baker et al, 2003(Baker et al, , 2009Lazovich et al, 2009) and poor quality of life can be long-lasting, since it has been shown that cancer survivors can experience physical and psychological symptoms for more than ten years following their treatment (Harrington et al, 2010). Research therefore has sought, and continues to seek, ways in which quality of life might be improved in this population group.…”
Section: Quality Of Lifementioning
confidence: 99%